Dopomóż najuboższym do przetrwania zimy i ofiaruj na pomoc zimową. (Tczew : [s.n.], 1947)
Afisz nawołujący do pomocy.
Keywords: Tczew (Polska) -- 1945-1970 -- druki ulotne; Tczew (Polska) -- 1945-1970 -- źródła